2004
DOI: 10.1055/s-2004-827210
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Correlation of St. John's Wort Extracts by Nuclear Magnetic Resonance Spectroscopy, Multivariate Data Analysis and Pharmacological Activity

Abstract: The use of proton NMR spectroscopy allows the analysis of complex multi-component mixtures such as plant extracts by simultaneous quantification of all proton-bearing compounds and consequently all relevant substance classes. Since the spectra obtained are too complicated to be analysed visually, the classification of spectra was carried out using multivariate statistical methods. The spectroscopic data of various extracts of St. John's wort (Hypericum perforatum) samples derived from 4 different accessions ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…In dereplication in studies for new leads from natural sources for drug development the metabolomics approach would be important to rapidly identify known actives. Finally one can also envisage the use of metabolomics approaches in the studies of the activity of medicinal plants (Roos et al, 2004;Mei Wang et al, 2005). By measuring the activity in a living organism (which can be anything from a cell culture, animals to patients) for extracts with different composition, possibly one may identify a compound or a combination of compounds that correlate with the activity.…”
Section: Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In dereplication in studies for new leads from natural sources for drug development the metabolomics approach would be important to rapidly identify known actives. Finally one can also envisage the use of metabolomics approaches in the studies of the activity of medicinal plants (Roos et al, 2004;Mei Wang et al, 2005). By measuring the activity in a living organism (which can be anything from a cell culture, animals to patients) for extracts with different composition, possibly one may identify a compound or a combination of compounds that correlate with the activity.…”
Section: Metabolomicsmentioning
confidence: 99%
“…The first steps on this route have been made, Roos et al (2004) analyzed different accessions and extracts of St. John's wort by means of NMR and correlated that with activity on the opioid receptor. Wang et al (2005) showed that chamomile ingestion during two weeks resulted in a clearly different NMR-profile of urine metabolites.…”
Section: Systems Biologymentioning
confidence: 99%
“…NMR 1 H NMR has been the predominant profiling method because it is fast and simple, and the technique has been used as a major analytical tool for many applications in plant metabolomics, such as quality control [20], chemotaxonomy (classification [7] and characterization [21,22]), analysis of the equivalence of genetically modified plants [23,24], and interaction with other organisms [25] and the environment [26]. NMR has lower sensitivity than MS so it is particularly useful when high sensitivity is not required, such as in the quality control of medicinal plants [27] and pharmaceutical preparations and tablets [28].…”
Section: What Does Metabolomics Analyze?mentioning
confidence: 99%
“…A validated regression model was built in deciding whether the bioactivity of a new set of OS extract could be hypothesized in relation between variables obtained from the regression analysis, without the necessity of having to do the bioassay [32]. The regression model, as represented by the data, was validated based on the coefficient of determination (R2 = 0.825) value, whereby most of the data lie near to the linear regression line of best fit line [32].…”
Section: Resultsmentioning
confidence: 99%
“…The regression model, as represented by the data, was validated based on the coefficient of determination (R2 = 0.825) value, whereby most of the data lie near to the linear regression line of best fit line [32]. The obtained 1 H NMR data of the plant extracts were used as the X variables and the relative concentration of glucose was used as the Y variable.…”
Section: Resultsmentioning
confidence: 99%